Proposing and assessing a software visualization approach based on polymetric views. (June 2016) - Francese, Rita; Risi, Michele; Scanniello, Giuseppe; Tortora, Genoveffa
Abstract: In this paper, we present an approach for the visualization of object-oriented software. This approach has been implemented in MetricAttitude, a visualization tool based on static analysis that provides a mental picture of a software implemented in Java by means of polymetric views. The approach graphically represents a suite of object-oriented design metrics (e.g., Weighted Methods per Class) and "traditional" code-size metrics (e.g., Lines Of Code). To assess the validity of our proposal, we have conducted two users' studies with students in Computer Science and professional software developers. The used empirical method is qualitative. To assess MetricAttitude and its underlying approach, we conducted questionnaire-based surveys. Results suggest that MetricAttitude is a viable means to deal with existing objects-oriented software and to comprehend their source code, in particular. Abstract : Highlights: We propose an approach for the visualization of object-oriented software. A software system is represented by polymetric views relied on statistical analysis. A software system overview in terms of size, complexity and structure is provided. Classes candidated for refactoring, important classes and hierarchies are highlighted. Two user studies with students and professional software developers are discussed.